Prozesky, M. 2019. Honest to Goodness: An Ethical and Spiritual Odyssey. Eugene: Resource Publications. 302 pages.Hardcover ISBN: 978-1-5326-6537-0 - Garth J. Mason (Journal for the Study of Religion)
Martin Prozesky’s book, Honest to goodness: An ethical and spiritual Odysseyis an ambitious project.